2014
DOI: 10.4161/cbt.29927
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic role of RREB1, ZIP3 zinc transporter, and zinc in human pancreatic adenocarcinoma

Abstract: Pancreatic cancer (ductal adenocarcinoma) remains a deadly cancer with ~85% mortality, and a 5-year survival rate of ~6% or less for the past 30 years. The factors and events associated with the development of pancreatic cancer are poorly identified. As such, effective biomarkers for early detection of malignancy are lacking. Efficacious chemotherapy once the cancer is identified does not exist. Recent clinical studies have revealed that the zinc levels are consistently and markedly decreased in adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Figure 5(a) shows that zinc uptake by PC-3 cells is dependent upon ZIP1 transporter, which increases zinc uptake and accumulation that inhibits cell proliferation [26]. Similarly, Figure 5(b) shows that physiological zinc treatment of Panc1 cells results in increased zinc and its inhibition of cell growth; and the dependency of zinc uptake on ZIP3 transporter [27]. Figure 5(c) shows that physiological zinc treatment of HepG2 cells results in zinc accumulation and its inhibition of cell growth [18].…”
Section: The Zip/zn Transformation and Zinc Toxicity In Malignant mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5(a) shows that zinc uptake by PC-3 cells is dependent upon ZIP1 transporter, which increases zinc uptake and accumulation that inhibits cell proliferation [26]. Similarly, Figure 5(b) shows that physiological zinc treatment of Panc1 cells results in increased zinc and its inhibition of cell growth; and the dependency of zinc uptake on ZIP3 transporter [27]. Figure 5(c) shows that physiological zinc treatment of HepG2 cells results in zinc accumulation and its inhibition of cell growth [18].…”
Section: The Zip/zn Transformation and Zinc Toxicity In Malignant mentioning
confidence: 99%
“…(b) Effects of physiological zinc treatment of Panc1 cells showing increased accumulation of zinc and its inhibition of cell growth. Reproduced from [27]. Also shows the dependency on ZIP3 transporter.…”
Section: Figurementioning
confidence: 99%
“…Ras responsive element binding protein 1 (RREB1) is an important transcription factor, which can initiate the transcription of many downstream genes once activated. It has been reported that RREB1 is associated with type 2 diabetes and tumor (16,17). However, the expression pattern and role of RREB1 in neuropathic pain remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in zinc, RREB1 transcription factor and ZIP3 zinc uptake transporter levels appears to be an early event in the development of pancreatic cancer. Franklin et al demonstrated that exposure of Panc1 cells to physiological concentrations of zinc results in increased zinc uptake and its accumulation also inhibits cell proliferation 21 . Absorption of zinc from the intestine may be hampered in patients of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%